Social and Media Impact of Communication Management in Male and Female Professional Soccer Teams in Ecuador - Americo, Marcos [UNESP]; Trujillo, Daniel Sebastian Flores [UNESP] (Univ Nacional Plata, Inst Investigaciones & Comunicacion-iicom, 2023)
In Ecuador, the men's and women's soccer teams have asymmetries, although both are professionals. While a player from a first division men's team earns on average at least $5,000, a player from a women's team earns a maximum of $400 (Ecuador's basic salary). This notable difference is also reflected in the management of team communication. A men's soccer team can have more than 50,000 followers on a social network like Instagram, while one of the best women's teams barely reaches 15,000, both in the top flight. These numbers have an impact, for example, on getting sponsors, generating specific sponsorships or seeking financial aid. In this work, data and statistics collected during a year in two soccer teams will be analyzed: one for men, Club Deportivo El Nacional; and one for women, Quito FC, both in the first division, to determine and clarify all the determinants for the existence of this gap between men's and women's teams, and possible solutions so that these differences can be reduced.
Keywords: men's and women's soccer; convergence; media; social networks